1972
DOI: 10.1111/j.1365-246x.1972.tb06102.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of the 40Ar/39Ar Stepwise Degassing Technique

Abstract: StepwiseThe principal advantage of the 40Ar/39Ar dating method lies in the stepwise degassing technique. Despite the widespread use of the technique, each worker seems to adopt an individual criterion of choice, as to how the data should be treated, so as to extract the maximum amount of information from it.It was considered desirable to make a detailed analysis of the data taken during a number of stepwise degassing experiments to decide upon the most useful treatment of results.The basic principles of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Ar 40 /Ar 39 measurements (Brereton, 1972) were made to determine if excess radiogenic Ar could be detected, thereby confirming the hypothesis that the 1-m.y. age is indeed too old because of incomplete Ar outgassing.…”
Section: Figure 2 Oxygen-isotope Curves Showing Youngest Oxygen-isotmentioning
confidence: 93%
See 1 more Smart Citation
“…Ar 40 /Ar 39 measurements (Brereton, 1972) were made to determine if excess radiogenic Ar could be detected, thereby confirming the hypothesis that the 1-m.y. age is indeed too old because of incomplete Ar outgassing.…”
Section: Figure 2 Oxygen-isotope Curves Showing Youngest Oxygen-isotmentioning
confidence: 93%
“…age is indeed too old because of incomplete Ar outgassing. The Ar 40 /Ar 39 stepwise degassing technique (Brereton, 1972) gave an age of about 260,000 yr for this ash, and the measurements indicated that excess radiogenic Ar was present (J. Dymond, 1973, oral commun. ).…”
Section: Figure 2 Oxygen-isotope Curves Showing Youngest Oxygen-isotmentioning
confidence: 98%
“…K-Ar isochrons, which not only allow for initial argon but may furnish objective internal criteria for discrepancy detection, and in this respect rival the expensive and the time consuming 40 Ar/ 39 Ar step heating method for single samples (Fitch, Miller & Mitchell, 1969;Bryhni, Fitch & Miller, 1971;Brereton, 1972;Fitch, 1972;Miller, 1972;. AH quoted ages are based on the following constants: A 3 = 4.72 x 10~1 0 y 1 , A e = 0.584 x 10-10 y-1 , and 40 K/K = 0.0119 at.…”
Section: Geo 113mentioning
confidence: 99%
“…(1) The saddle-shaped age spectra have been presented by several authors (e.g., Lanphere and Dalrymple, 1971;Brereton, 1972;Kaneoka, 1974;Lanphere and Dalrymple, 1976). Lanphere and Dalrymple (1971) reported However, no definite criteria for the evaluation of disturbed 40 Ar- 39 Ar age results have been established.…”
Section: Introductionmentioning
confidence: 99%